A phase II trial of regorafenib in patients with advanced Ewing sarcoma and related tumors of soft tissue and bone: SARC024 trial results. (10th August 2022) - Attia, Steven; Bolejack, Vanessa; Ganjoo, Kristen N.; George, Suzanne; Agulnik, Mark; Rushing, Daniel; Loggers, Elizabeth T.; Livingston, Michael B.; Wright, Jennifer; Chawla, Sant P.; Okuno, Scott H.; Reinke, Denise K.; et al.
Abstract: Background: Regorafenib is one of several FDA‐approved cancer therapies targeting multiple tyrosine kinases. However, there are few subtype‐specific data regarding kinase inhibitor activity in sarcomas. We report results of a single arm, phase II trial of regorafenib in advanced Ewing family sarcomas. Methods: Patients with metastatic Ewing family sarcomas (age ≥ 18, ECOG 0–2, good organ function) who had received at least one line of therapy and experienced progression within 6 months of registration were eligible. Prior kinase inhibitors were not allowed. The initial dose of regorafenib was 160 mg oral days 1–21 of a 28‐day cycle. The primary endpoint was estimating progression‐free rate (PFR) at 8 weeks employing RECIST 1.1. Results: Thirty patients (median age, 32 years; 33% women [10 patients]; bone primary, 40%; extraskeletal primary, 60%) enrolled at 14 sites. The most common grade 3 or higher toxicities were hypophosphatemia (5 grade 3, 1 grade 4), hypertension (2 grade 3), elevated ALT (2 grade 3). Sixteen patients required dose reductions, most often for hypophosphatemia ( n = 7 reductions in 6 patients); two stopped regorafenib for toxicity. There was one death unrelated to treatment in the 30‐day post‐study period. Median progression‐free survival (PFS) was 14.8 weeks (95% CI 7.3–15.9); PFR at 8 weeks by Kaplan–Meier analysis was 63% (95% CI 46–81%). The RECIST 1.1 response rate was 10%. Median OS was 53 weeks (95% CI 37–106 weeks). Conclusions: Regorafenib has modest activity in the Ewing family sarcomas. Toxicity was similar to that seen in approval studies. Abstract : This single arm phase II study of regorafenib in adults with advanced Ewing sarcoma met its primary endpoint of 8 week progression‐free survival rate of 73%. The RECIST 1.1 response rate was 10%.